Phage-antibiotic combinations in various treatment modalities to manage MRSA infections - Loganathan, Archana; Bozdogan, Bulent; Manohar, Prasanth; Nachimuthu, Ramesh (Frontiers in Pharmacology, 2024)
Introduction: The emergence of antibiotic resistance is a significant challenge in the treatment of bacterial infections, particularly in patients in the intensive care unit (ICU). Phage-antibiotic combination therapy is now being utilized as a preferred therapeutic option for infections that are multi-drug resistant in nature. Methods: In this study, we examined the combined impact of the staph phage vB_Sau_S90 and four antibiotics on methicillin-resistant Staphylococcus aureus (MRSA). We conducted experiments on three different treatment sequences: a) administering phages before antibiotics, b) administering phages and antibiotics simultaneously, and c) administering antibiotics before phages. Results: When the media was supplemented with sub-inhibitory concentrations of 0.25 μg/mL and 1 μg/mL, the size of the plaque increased from 0.5 ± 0.1 mm (in the control group with only the phage) to 4 ± 0.2 mm, 1.6 ± 0.1 mm, and 1.6 ± 0.4 mm when fosfomycin, ciprofloxacin, and oxacillin were added, respectively. The checkerboard analysis revealed a synergistic effect between the phages and antibiotics investigated, as indicated by a FIC value of less than 0.5. The combination treatment of phages and antibiotics demonstrated universal efficacy across all treatments. Nevertheless, the optimal effectiveness was demonstrated when the antibiotics were delivered subsequent to the phages. Utilizing the Galleria mellonella model, in vivo experiments showed that the combination of phage-oxacillin effectively eliminated biofilm-infected larvae, resulting in a survival rate of up to 80% in the treated groups. Discussion: Our findings highlight the advantages of using a combination of phage and antibiotic over using phages alone in the treatment of MRSA infections.